Immunomodulator triptolide synergizes with black phosphorus nanosheets-mediated calcium overload for mild heat-potentiated cancer immunotherapy - Guoping Jia; Huizhen Yang; Qinghe Wu; Yifei Jiang; He Gao; Xubo Wu; Zhiyuan Xie; Haizhen Jin; Jia Xu; Chunfu Zhang (Chemical Engineering Journal, 2026)

Identification of HsfA9 and a network of regulators involved in resistance to bacterial wilt under high temperature in tomato - Jing Li; Wenhao Zhong; Qiaoping Mo; Xiaoyu Qi; Juan Li; Hongling Yang; Jianghua Cai; Mengyun Xu; Guoping Wang (Plant Science, 2026)

Human sweet, umami and bitter taste receptors: From decoders of taste perception to sentinels of systemic metabolism and health - Yuxiang Gu; Yixuan Cui; Kangli Guo; Guoping Zhao; Xing Li; Weixi Yang; Yanbo Wang (Trends in Food Science & Technology, 2026)

Bacteria–polysaccharide interfacial regulation by calcium alginate hydrogel capsules supports sulfate reduction in acidic water - Yujie Wang; Fangzhou Luo; Zhaoyue Yang; Zhenghua Liu; Huachan Lin; Xiyu Liu; Min Zhang; Guoping Jiang; Lei Zhou; Lechang Xu; Delong Meng; Qingyun Yan; et al. (Carbohydrate Polymers, 2026)

Evolution and functional characterization of the MdSKP8 gene as a conserved hub integrating hormone and antioxidant pathways for salt tolerance in apple - Miao Shao; Yongqing Feng; Shixiong Lu; Shangwen Yang; Jian Li; Xinyu Li; Zonghuan Ma; Guoping Liang; Baihong Chen; Juan Mao (Plant Cell Reports, 2026)

The relationship between micro-fragmentation mechanisms and macro-mechanical responses in granite residual soil - Bingxiang Yuan; Xiangwen Deng; Peng Luo; Xueqiang Yang; Jim Shiau; Xiaoyu Bai; Mayao Cheng; Guoping Lei; Junjie Zheng (Transportation Geotechnics, 2026)

Pollen-based response patterns of vegetation dynamics to environmental changes during the early-mid Holocene in the Ningshao Plain, China - Zhen Li; Chunmei Ma; Zijing She; Haiyan Li; Konglan Shao; Bin Zhou; Zhujun Hu; Qing Yang; Guoping Sun; Michael Meadows; Hongbo Zheng (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

VvGA2ox8-Like from grape confers drought tolerance by activating the antioxidant defense system - Wenqi Yang; Juanbo Yang; Shixiong Lu; Huimin Gou; Ning Wang; Miao Yuan; Weifeng Ma; Baozhen Zeng; Guoping Liang; Juan Mao (Plant Cell Reports, 2026)

Integrated metabolomics and transcriptomics analyses reveal the molecular mechanism of anthocyanin accumulation in veins and leaves of Broussonetia papyrifera under cold stress - Xiangxue Yu; Rui Ni; Dingguo Zhang; Bo Chen; Qian Li; Ziyu Yang; Chenjing Li; Fuyuan Liu; Yongtao Xia; Guoqing Hou; Guoping Wang; Pengzhi Mao; et al. (Plant Science, 2026)

Epilepsy associated with unusual white matter hyperintensity growth in a cerebral developmental venous anomaly - Lingjia Xu; Guoping Fu; Yang Zhou (Acta Neurologica Belgica, 2026)

Discovery and implications of the Late Carboniferous Tasensu gabbro–gabbrodiorite–granodiorite–monzogranite bimodal intrusions in Xiwuqi, Inner Mongolia, China - Wenjing Yang; Tianshe Cheng; Xuebin Zhang; Xiangqian He; Guoping Wang; Xujiang Cheng; Linhai Wang; Lijun Guo; Xingfang Duo; Hongsheng Gao (Journal of Volcanology and Geothermal Research, 2026)

Excellent infrared radiation performance and significant energy-saving efficiency of LaAlO3 ceramics via Ca2+/Co2+ co-doping - Qinghu Wang; Yangxi Liu; Guoping Wei; Liang Huang; Xueqing Wang; Shaobai Sang; Yibiao Xu; Xiong Liang; Yawei Li; Jiangtao Li; Olena Volkova; Emad M.M. Ewais; et al. (Chemical Engineering Journal, 2026)

Rigid-flexible-thermal coupling dynamic modeling and attitude control of large spaceborne deployable parabolic truss antenna - Shijie Zhou; Zhen Yang; Kaicheng Zhang; Xiang Liu; Guoping Cai (Advances in Space Research, 2026)

Development of a photocatalytic mesh system for high-efficiency wastewater purification under real weather conditions: Unveiling hydrodynamic-optical synergy and application potential - Cheng Zhang; Guangqi An; Yunxin Zhu; Zhenghao Wu; Wen Wei; Wenbin Jiang; Guoping Chen; Yingnan Yang (Chemical Engineering Journal, 2026)

Unraveling cross-variations in fruit aroma and color during ‘Red Delicious’ bud sport: Insights from targeted metabolomics and transcriptomics - Miao Shao; Yongqing Feng; Shangwen Yang; Huimin Gou; Xin Li; Zonghuan Ma; Guoping Liang; Baihong Chen; Juan Mao (Food Chemistry, 2025)

Highly efficient biophotoelectrochemical methanogenesis coupling with water sterilization via robust interfacial electronic communication - Jing Hu; Chaohui Yang; Yaping Qi; Mingqiu Hong; Jiajing Chen; Guoping Ren; Jie Ye (Chemical Engineering Journal, 2025)

Dynamically programmable plant-derived scaffold coordinates alveolar bone repair cascade: Phase-adaptive integration from hemostasis to bone remodeling - Yeke Chen; Yumei Ning; Fang Dai; Yuting Yang; Chenjiang He; Kaiqiang Yang; Yichen Hu; Guoping Cheng; Li Song (Chemical Engineering Journal, 2025)

Study of on-orbit thermally induced dynamic response of large spaceborne deployable parabolic truss antenna system - Shijie Zhou; Zhen Yang; Kaicheng Zhang; Xiang Liu; Guoping Cai (Advances in Space Research, 2025)

A dual solar-utilization photocatalytic mesh reactor for efficient harmful algal bloom control in real-world conditions: Performance, mechanism and global deployment - Guangqi An; Cheng Zhang; Yunxin Zhu; Ayaka Yoshii; Hongjian Zhang; Guoping Chen; Yingnan Yang (Chemical Engineering Journal, 2025)

The dynamic mechanism of north-south tectonic disparities in the Rakhine Offshore Basin of Myanmar - Xuefeng Wang; Gui Fang; Hongping Wang; Guozhang Fan; Guoping Zuo; Xiaoyong Xu; Zhili Yang (Frontiers in Marine Science, 2025)
The Rakhine Offshore Basin is located within an accretionary wedge in the trench setting of an active continental margin, exhibiting complex and dynamic characteristics. Its structure is notably segmented from north to south and zoned from east to west. The basin is divided into two segments along the north-south axis: the northern segment features a compressional fold belt, while the southern segment is characterized by a strike-slip belt. Along the east-west axis, the basin is divided into two zones: the eastern zone represents the early-stage, steeply folded belt, where the shallow part is disrupted by thrust faults, while the western zone is marked by later, gentle sedimentary structure. Despite these detailed structural observations, current research on the structural and evolutionary characteristics of the Rakhine Offshore Basin is still limited, and the underlying causes of its north-south segmentation and east-west zonation remain unclear. Using seismic and drilling data, we provide a comprehensive examination of the structural and evolutionary characteristics of the basin. The results indicate that the Rakhine Offshore Basin formed at the end of the Upper Cretaceous, experiencing significant deformation from the end of the Upper Miocene to the Quaternary. The structural formation progressed from east to west, occurring earlier and more intensely in the east, and later and more gently in the west. After Miocene sedimentation, the regional structure underwent inversion, with the depocenter migrating from east to west. The segmentation from north to south and zonation from east to west in the Rakhine Offshore Basin are attributed to the oblique subduction and collision of the Indian Ocean plate with the Eurasian plate. The subduction angle is gentler in the south and steeper in the north, reflecting varying stress field mechanisms across these regions.

Solar-light-driven inactivation of toxigenic Microcystis by floating photocatalytic mesh system: Insights on physiological mechanism and application - Guangqi An; Cheng Zhang; Yunxin Zhu; Hongjian Zhang; Naoki Kawazoe; Guoping Chen; Yingnan Yang (Water Research, 2025)

Unlocking the bioremediation potential of adapted Desulfovibrio desulfuricans in acidic low-temperature U-contaminated groundwater - Lei Zhou; Nan Bai; Rui Xiao; Zhendong Yang; Guoping Jiang; Huaqun Yin; Yujie Wang; Liangzhi Li; Delong Meng; Zhenghua Liu (Journal of Environmental Sciences, 2025)

Unveiling the components, physiological functions and emerging trends of hydroxycinnamic acid amides in goji berry (Lycium) - Siyuan Wei; Yuying Wang; Shiyu Zhou; Shina Luo; Yunuo Lin; Ruixi Wang; Qinyue Jia; Tingting Feng; Guoping Zhao; Xuefeng Yin; Fangwei Yang (Food Research International, 2025)

Enhanced deep denitrification for high-salinity wastewater treatment by constructing biofilm-based technology - Kun Ding; Shan Yang; Hao Hu; Zhenghao Li; Haoran Duan; Xiaoqiang Chen; Yankun Liu; Guoping Sheng (Journal of Environmental Management, 2025)

Effect of steaming on the selenium form, structure, and bioavailability of selenopolysaccharides from Chlamys nobilis - Junyang Yang; Junting Cai; Zhongqin Chen; Mingtang Tan; Huina Zheng; Jialong Gao; Haisheng Lin; Guoping Zhu; Wenhong Cao (Food Chemistry, 2025)

Enhanced hydrological disturbance and atmospheric pollution on an ombrotrophic peatland (Greater Khingan Mountains, Northeast China) since 1950s inferred from diatom records - Dongxue Han; Yang Sun; Jinxin Cong; Guoping Wang; Chuanyu Gao (Anthropocene, 2025)

Wood-inhabiting fungal community characteristics responses to nutrient additions vary among tree taxonomic groups - Xian He; Teng Yang; Katja T. Rinne-Garmston; Xiangyu Ji; Qian Xu; Zhiyuan Xu; Yuxiong Zheng; Zhuqi Zhao; Guoping Zhao; Zhenhong Hu (Journal of Soils and Sediments, 2025)

Generative adversarial network integrated with metabolomics identifies potential biomarkers related to quality changes of atemoya (Annona cherimola × Annona squamosa) stored at 10 and 25 °C - Ruoyan Zhang; Yu Zhong; Dangfeng Wang; Liang Gong; Linnan Yang; Feng Guo; Guoping Zhou; Yun Deng (Food Chemistry, 2025)

Microbial mechanisms of sulfate reduction for low-temperature bioremediation of acid-mined uranium sandstone groundwater - Rui Xiao; Zhenghua Liu; Min Xu; Guoping Jiang; Yang Peng; Cunzeng Li; Jie Wang; Huaqun Yin; Lechang Xu (Journal of Water Process Engineering, 2025)

Synergy of Fe-modified zeolite and light stimulation on ammonia-stressed anaerobic digestion: Performance, microbial community and metabolic pathway - Zhiyuan Liu; Yunxin Zhu; Mingyuan Sun; Guangqi An; Jingwei Yang; Cheng Zhang; Guoping Chen; Yingnan Yang (Chemical Engineering Journal, 2025)

Nitrogen addition promotes soil carbon accumulation globally - Xuemei Yang; Suhui Ma; Erhan Huang; Danhua Zhang; Guoping Chen; Jiangling Zhu; Chengjun Ji; Biao Zhu; Lingli Liu; Jingyun Fang (Science China Life Sciences, 2025)

Peanut–cotton intercropping to enhance soil ecosystem multifunctionality: Roles of microbial keystone taxa, assembly processes, and C-cycling profiles - Shijie Zhang; Yingchun Han; Guoping Wang; Lu Feng; Yaping Lei; Shiwu Xiong; Beifang Yang; Xiaoyu Zhi; Minghua Xin; Yahui Jiao; Xiao-Fei Li; Yabing Li; et al. (Agriculture, Ecosystems & Environment, 2025)

Pharmacokinetic-pharmacodynamic Modelling of NH600001 in Healthy Subjects and Patients Undergoing Gastroscopy - Yaxin Liu; Yun Kuang; Jie Huang; Dan Jiang; Yajie Cao; Qi Gao; Zifeng Li; Wen Ouyang; Saiying Wang; Qi Pei; Guoping Yang (The AAPS Journal, 2024)

The knockout of SlMTC impacts tomato seed size and reduces resistance to salt stress in tomato - Zihan Gao; Qingling Yang; Hui Shen; Pengyu Guo; Qiaoli Xie; Guoping Chen; Zongli Hu (Plant Science, 2024)

Impact of metals exposure on lung function and serum club cell secretory protein among schoolchildren: A mixture and mediation analysis - Jie Li; Meili Shen; Ting Wang; Xiao Zhang; Wen Gu; Mengmeng Xu; Tongjin Yang; Jie Cui; Xin Xia; Guoping Chen; Siyu Zheng; Haoying Yang; et al. (Journal of Hazardous Materials, 2024)

Evolution of phosphate metabolism in Tibetan wild barley to adapt to aluminum stress - Shengguan Cai; Yuqing Huang; Yang Liu; Liyuan Wu; Dezhi Wu; Rong Liu; Peter R. Ryan; Meixue Zhou; Guoping Zhang; Zhong-Hua Chen (Plant and Soil, 2024)

Distribution and response of electroactive microorganisms to freshwater river pollution - Shan Yang; Meijun Dong; Lizhou Lin; Bo Wu; Youda Huang; Jun Guo; Guoping Sun; Shaofeng Zhou; Meiying Xu (Environmental Pollution, 2024)

Fe-mordenite for high-performance N2 rejection - Zhi Yu; Jianing Yang; Seyed Hesam Mousavi; Penny Xiao; Xue Yan; Ali Zavabeti; Yongqiang Wang; Kaifei Chen; Zhe Jefferson Liu; Guoping Hu; Xiaoling Liu; Yu Zhou; et al. (Chemical Engineering Journal, 2024)

Development of a sunlight adjustable parabolic trough reactor for 24-hour efficient photocatalytic wastewater treatment - Cheng Zhang; Guangqi An; Yunxin Zhu; Xiang Sun; Guoping Chen; Yingnan Yang (Chemical Engineering Journal, 2024)

Co-composting of dewatered sludge and wheat straw with newly isolated Xenophilus azovorans: Carbon dynamics, humification, and driving pathways - Xuan Wu; Runyu Gao; Xiaorui Tian; Jiawei Hou; Yang Wang; Quan Wang; Daniel Kuok Ho Tang; Yiqing Yao; Xiu Zhang; Bowen Wang; Guoping Yang; Hua Li; et al. (Journal of Environmental Management, 2024)

Genome-wide transcriptome analyses reveal changes in glutathione-overproducing yeast obtained by ARTP mutagenesis for rice wine brewing - Yao Yang; Charles Obinwanne Okoye; Jiahui Xiang; Wei Huang; Yuyang Liu; Ronghai He; Guoping Huang; Haile Ma (Food Bioscience, 2024)

Improving Granulosa Cell Function in Premature Ovarian Failure with Umbilical Cord Mesenchymal Stromal Cell Exosome-Derived hsa_circ_0002021 - Ge Yang; Bo Zhang; Mei Xu; MingJun Wu; Jie Lin; ZiYu Luo; YueHua Chen; Qin Hu; GuoPing Huang; HaiYan Hu (Tissue Engineering and Regenerative Medicine, 2024)

m6A-Mediated Upregulation of lncRNA CHASERR Promotes the Progression of Glioma by Modulating the miR-6893-3p/TRIM14 Axis - Xingwei Wu; Minjie Fu; Chang Ge; Hanyu Zhou; Haoyu Huang; Min Zhong; Mengying Zhang; Hao Xu; Guoping Zhu; Wei Hua; Kun Lv; Hui Yang (Molecular Neurobiology, 2024)

Establishing Virtual Bioequivalence and Clinically Relevant Specifications for Omeprazole Enteric-Coated Capsules by Incorporating Dissolution Data in PBPK Modeling - Ruwei Yang; Yaqi Lin; Kaifeng Chen; Jie Huang; Shuang Yang; An Yao; Xiaoyan Yang; Deqing Lei; Jing Xiao; Guoping Yang; Qi Pei (The AAPS Journal, 2024)

A circular single-stranded DNA mycovirus infects plants and confers broad-spectrum fungal resistance - Xianhong Wang; Ioly Kotta-Loizou; Robert H.A. Coutts; Huifang Deng; Zhenhao Han; Ni Hong; Karim Shafik; Liping Wang; Yashuang Guo; Mengmeng Yang; Wenxing Xu; Guoping Wang (Molecular Plant, 2024)

The impact of ammonifying microorganisms on the stabilization and carbon conversion of cow manure and wheat husk co-composting - Zhiming Xu; Ronghua Li; Jun Liu; Xuerui Xu; Shaowen Wang; Feng Gao; Guoping Yang; Yiqing Yao; Zengqiang Zhang; Xiu Zhang; Yong Zhang; Fusheng Quan (Chemical Engineering Journal, 2024)

Film-straw dual mulching improves soil fertility and maize yield in dryland farming by increasing straw-degrading bacterial abundance and their positive cooperation - Fengke Yang; Baolin He; Bo Dong; Guoping Zhang (Agriculture, Ecosystems & Environment, 2024)

When healthy aging meets Vitamin G: Assessing the associations between green space and heart health in older adults using street view and electrocardiography - Ruoyu Wang; Guoping Dong; Yang Zhou; Tongyun Du; Guang-Hui Dong; Marco Helbich (Landscape and Urban Planning, 2024)

Increased overyielding probability and yield stability from a 5-year cotton-based intercropping - Yurui Tang; Yurong Qiu; Xin Li; Haoyue Qin; Jian Wang; Shijie Zhang; Yingchun Han; Lu Feng; Guoping Wang; Beifang Yang; Yaping Lei; Shiwu Xiong; et al. (European Journal of Agronomy, 2024)

Highly efficient thermal decomposition of AP through intimately encapsulating in 3DOM CoFe2O4 spinel - Desheng Yang; Chaofei Bai; Fengdan Zhu; Chang Liu; Cheng Zhao Tu; Guoping Li; Yunjun Luo; Tianfu Zhang (Chemical Engineering Journal, 2024)

Effects of two strains of thermophilic nitrogen-fixing bacteria on nitrogen loss mitigation in cow dung compost - Shaowen Wang; Zhiming Xu; Xuerui Xu; Feng Gao; Kang Zhang; Xin Zhang; Xiu Zhang; Guoping Yang; Zengqiang Zhang; Ronghua Li; Fusheng Quan (Bioresource Technology, 2024)

Significance of homogeneous operation in light-assisted fixed-bed bioprocess under ammonia stress: Optimization, long-term operation and metagenomic analysis - Yunxin Zhu; Yujia Chen; Guangqi An; Cheng Zhang; Jingwei Yang; Rongyong Yang; Guoping Chen; Yingnan Yang (Bioresource Technology, 2024)

Mechanistic study on the promotion of Ca2+ leaching in steel slag through high-temperature solid waste modification - Dongfeng He; Liu Yang; Yinbo Luo; Hongbo Zhao; Guoping Liu; Zhanjun Wu (Environmental Science and Pollution Research, 2024)

Insight into the humification and carbon balance of biogas residual biochar amended co-composting of hog slurry and wheat straw - Yunpeng Liu; Junting Pan; Jingwen Wang; Xu Yang; Wanqiang Zhang; Kuok Ho Daniel Tang; Hailong Wang; Xiu Zhang; Runyu Gao; Guoping Yang; Zengqiang Zhang; Ronghua Li (Environmental Science and Pollution Research, 2024)

Why do anaerobes like the light stimulation: Enhanced anaerobic digestion at different wavelengths under ammonia stress - Yunxin Zhu; Guangqi An; Cheng Zhang; Guoping Chen; Yingnan Yang (Chemical Engineering Journal, 2024)

Pelargonidin alleviates acrolein-induced inflammation in human umbilical vein endothelial cells by reducing COX-2 expression through the NF-κB pathway - Youping Wan; Han Yang; Guoping Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Dynamic Changes in Rhizosphere Microbial Communities of Watermelon During Continuous Monocropping with Gravel Mulch - Tingting Shen; Xiu Zhang; Li Li; Yuxi Qi; Hongfei Ji; Guoping Yang; Xue-Xian Zhang (Journal of Soil Science and Plant Nutrition, 2024)

Biotic and abiotic effects of manganese salt and apple branch biochar co-application on humification in the co-composting of hog manure and sawdust - Xuan Wu; Xinyu Zhao; Weilong Wu; Jiawei Hou; Wanqiang Zhang; Daniel Kuok Ho Tang; Xiu Zhang; Guoping Yang; Zengqiang Zhang; Yiqing Yao; Ronghua Li (Chemical Engineering Journal, 2024)

Simultaneous decontamination of phosphorus and bisphenol A from livestock wastewater with boehmite-modified carbon composite - Yaru Peng; Xiu Zhang; Yuan Luo; Azeem Muhammad; Guoping Yang; Kuok Ho Daniel Tang; Zengqiang Zhang; Yuan Xu; Menghao Li; Jintong Cui; Ronghua Li (Bioresource Technology, 2024)

Biochemical tracers in spiny icefish (Chaenodraco wilsoni) as indicators of variability in the diet of Antarctic krill (Euphausia superba) in a highly dynamic environment - Qingyuan Yang; Guoping Zhu (Journal of Marine Systems, 2024)

Efficient self-cleaning and antibacterial ceramics with ultra-low doping and high exposure of silver - Kaibo Hu; Chuanqi Zhang; Guobiao Li; Yucheng Liu; Dong Wang; Ke Li; Guoping Hu; Liuyimei Yang; Yinhua Wan (Journal of Hazardous Materials, 2024)

Mechanism of Diabatic Heating on Precipitation and the Track of a Tibetan Plateau Vortex over the Eastern Slope of the Tibetan Plateau - Yuanchang Dong; Guoping Li; Xiaolin Xie; Long Yang; Peiwen Zhang; Bo Zeng (Advances in Atmospheric Sciences, 2024)

Explaining nitrogen turnover in sediments and water through variations in microbial community composition and potential function - Shan Yang; Meijun Dong; Huibin Lu; Zhipeng Cai; Meng Ge; Jia Xing; Haobin Huang; Youda Huang; Guoping Sun; Shaofeng Zhou; Meiying Xu (Chemosphere, 2023)

Photocatalytic degradation of multiple-organic-pollutant under visible light by graphene oxide modified composite: degradation pathway, DFT calculation and mechanism - Qiansu Ma; Jie Ming; Xiang Sun; Hongjian Zhang; Guangqi An; Naoki Kawazoe; Guoping Chen; Yingnan Yang (Journal of Environmental Management, 2023)

Overexpression of SlPRE3 alters the plant morphologies in Solanum lycopersicum - Pengyu Guo; Qingling Yang; Yunshu Wang; Zhijie Yang; Qiaoli Xie; Guoping Chen; Xuqing Chen; Zongli Hu (Plant Cell Reports, 2023)

Formation of natural fractures and their impact on shale oil accumulation in the Mahu Sag, Junggar Basin, NW China - Xiaoyu Du; Zhijun Jin; Lianbo Zeng; Guoping Liu; Wenjun He; Mehdi Ostadhassan; Yong Song; Xinping Liang; Sen Yang; Guoqing Lu (International Journal of Coal Geology, 2023)

Directly linking plant N, P and K nutrition to biomass production in cotton-based intercropping systems - Yurong Qiu; Xin Li; Yurui Tang; Shiwu Xiong; Yingchun Han; Zhanbiao Wang; Lu Feng; Guoping Wang; Beifang Yang; Yaping Lei; Wenli Du; Xiaoyu Zhi; et al. (European Journal of Agronomy, 2023)

Development and validation of 105 SNP markers in Chionodraco rastrospinosus - Yewei Yu; Yang Liu; Guoping Zhu; Congcong Wang (Conservation Genetics Resources, 2023)

Assessing the performance of SWAN model for wave simulations in the Bay of Bengal - Wanwei Zhang; Hongjun Zhao; Guoping Chen; Jie Yang (Ocean Engineering, 2023)

Characteristics and controlling factors of natural fractures in deep lacustrine shale oil reservoirs of the Permian Fengcheng Formation in the Mahu Sag, Junggar Basin, China - Xiaoyu Du; Zhijun Jin; Lianbo Zeng; Guoping Liu; Wenjun He; Mehdi Ostadhassan; XinPing Liang; Sen Yang; Guoqing Lu (Journal of Structural Geology, 2023)

Photochemical transformation of terrestrial dissolved organic matter derived from multiple sources in tropical plantations - Gege Yin; Peng Zhang; Yinghui Wang; Bilal Aftab; Penghui Du; Qiang Zhang; Guoping Chen; Mengke Wang; Biwei Yang; Senhao Wang; Jiangming Mo; Wei Zhang; et al. (Geochimica et Cosmochimica Acta, 2023)

Mycobacteriaceae Phenome Atlas (MPA): A Standardized Atlas for the Mycobacteriaceae Phenome Based on Heterogeneous Sources - Wan Liu; Hui Cen; Zhile Wu; Haokui Zhou; Shuo Chen; Xilan Yang; Guoping Zhao; Guoqing Zhang (Phenomics, 2023)
The bacterial family Mycobacteriaceae includes pathogenic and nonpathogenic bacteria, and systematic research on their genome and phenome can give comprehensive perspectives for exploring their disease mechanism. In this study, the phenotypes of Mycobacteriaceae were inferred from available phenomic data, and 82 microbial phenotypic traits were recruited as data elements of the microbial phenome. This Mycobacteriaceae phenome contains five categories and 20 subcategories of polyphasic phenotypes, and three categories and eight subcategories of functional phenotypes, all of which are complementary to the existing data standards of microbial phenotypes. The phenomic data of Mycobacteriaceae strains were compiled by literature mining, third-party database integration, and bioinformatics annotation. The phenotypes were searchable and comparable from the website of the Mycobacteriaceae Phenome Atlas (MPA, https://www.biosino.org/mpa/ ). A topological data analysis of MPA revealed the co-evolution between Mycobacterium tuberculosis and virulence factors, and uncovered potential pathogenicity-associated phenotypes. Two hundred and sixty potential pathogen-enriched pathways were found by Fisher's exact test. The application of MPA may provide novel insights into the pathogenicity mechanism and antimicrobial targets of Mycobacteriaceae.

Contrasting responses of spatiotemporal patterns of cropland to climate change in Northeast China - Ziyang Yu; Zhenzhen Li; Haoxuan Yang; Yihao Wang; Yang Cui; Guoping Lei; Shuai Ye (Food Security, 2023)

Diatom evidence for late Holocene environmental change in a permafrost peatland in the northern Greater Khingan Mountains, Northeast China - Dongxue Han; Yang Sun; Zicheng Yu; Ming Jiang; Jinxin Cong; Chuanyu Gao; Guoping Wang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Dopamine/β-cyclodextrin synergistically modified core-shell MF@ZIF-8 porous membrane for high-efficient filtering of particulate matter (PM) in air and gathering oil in water - Zerong He; Nan Hu; Xiaoyun Meng; Jiang Li; Qi Wu; Guoping Yang; Wenyan Zhang; Yaoyu Wang (Chemical Engineering Journal, 2023)

Assessing Spatio-Temporal Variability of Soil Phosphorus in Different Cotton-Based Cropping Systems Using Geo-Statistics - Li Teng; Xiong Shiwu; Wang Zhanbao; Li Xiaofei; Han Yingchun; Wang Guoping; Lei Yaping; Feng Lu; Yang Beifang; Zhi Xiaoyu; Fan Zhengyi; Li Yabing (Journal of Soil Science and Plant Nutrition, 2023)

Regulatory miRNAs, circRNAs and lncRNAs in cell cycle progression of breast cancer - Huan Chen; Guoping Xie; Qunying Luo; Yisha Yang; Siheng Hu (Functional & Integrative Genomics, 2023)

Optimizing plant type structure to adjust the temporal and spatial distribution of water consumption and promote the growth and yield formation of cotton - Yaru Wang; Jiale Chen; Fengqi Wu; Beifang Yang; Yingchun Han; Lu Feng; Zhanbiao Wang; Xiaofei Li; Yaping Lei; Shiwu Xiong; Guoping Wang; Xiaoyu Zhi; et al. (European Journal of Agronomy, 2023)

An effective pretreatment technique based on multi-walled carbon nanotubes to reduce the matrix effect in plasma samples analyzed by a new type probe electrospray ionization method - Zhenwei Xiao; Yunhui Xing; Janshon Zhu; Yang Liu; Jinxingyi Wang; Qian Liu; Min Huang; GuoPing Zhong (Analytica Chimica Acta, 2023)

The influence of cold filaments on the evolution of dipole structures - Qi Yang; Guihua Wang; Chi Xu; Guoping Gao; Ruili Sun (Frontiers in Marine Science, 2023)
Mesoscale eddy dipoles are oceanographic structures that can transport ocean water parcels horizontally and vertically in ways that differ from individual mesoscale eddies. The most conspicuous additional feature that presents in dipoles is the cold filament (CF) that can be spontaneously generated between a dipole’s anticyclonic eddy (AE) and cyclonic eddy (CE). A case study in this paper shows that the interaction between the CF and the CE component of the dipole is associated with the structural evolution of the dipole. This interaction is verified in synthesis and normalization studies of the CF dipoles. The CF-dipole interaction entrains CF water into the center of the dipole’ CE and leads to a cold and high chlorophyll center in the upper layer of the CE. The formation of this cold center changes the dipole’s structure by eliminating the phase difference between the thermal and dynamic centers of the dipole. The entrainment also provides a new mechanism for the development of high chlorophyll levels in the CE. In the analysis of the HYCOM (Hybrid Coordinate Ocean Model) simulation of a synthetic CF dipole, the AE has a three-zone structure while the CE only has two. The convergence of the CE’s outermost zone results in a biased interaction.

Development of a green and efficient photocatalytic mesh microalgae biorefinery (PMMB) system for sustainable biomass conversion under real solar light - Cheng Zhang; Jie Ming; Xiang Sun; Yunxin Zhu; Guangqi An; Guoping Chen; Yingnan Yang (Chemical Engineering Journal, 2023)

Dual role of soil-derived dissolved organic matter in the sulfamethoxazole oxidation by manganese dioxide - Biwei Yang; Penghui Du; Guoping Chen; Peng Zhang; Qiang Zhang; Zhongying Wang; Gan Zhang; Zongwei Cai; Junjian Wang (Water Research, 2023)

The nitrogen footprint and reactive nitrogen reduction potential of cotton production in China - Weibin Huang; Fengqi Wu; Zhenggui Zhang; Yongming Meng; Jian Wang; Qinqin Li; Yingchun Han; Lu Feng; Xiaofei Li; Guoping Wang; Yaping Lei; Zhengyi Fan; et al. (Journal of Cleaner Production, 2023)

Evaluation of MACC total aerosol optical depth and its correction model based on the random forest regression - Yang Zhen; Guoping Shi (Theoretical and Applied Climatology, 2023)

Pyridine N of N/Co-co-doped graphite gas diffusion electrode facilitating the efficient production of hydroxyl radicals in the electro-peroxone process - Qiang Bi; Sisi Jiang; Changfeng Hu; Li Zhang; Yilin Zhao; Bo Yang; Guoping Li; Juanqin Xue (Journal of Environmental Chemical Engineering, 2023)

Orychophragmus violaceus/cotton relay intercropping with reduced N application maintains or improves crop productivity and soil carbon and nitrogen fractions - Zhenggui Zhang; Jian Wang; Shiwu Xiong; Weibin Huang; Xiaofei Li; Minghua Xin; Yingchun Han; Guoping Wang; Lu Feng; Yaping Lei; Beifang Yang; Yabing Li; et al. (Field Crops Research, 2023)

Advanced photocatalytic sterilization for recalcitrant Enterococcus sp. contaminated water by newly developed Z-scheme Bi2WO6 based composites under solar light - Jie Ming; Xiang Sun; Qiansu Ma; Na Liu; Cheng Zhang; Naoki Kawazoe; Guoping Chen; Yingnan Yang (Chemosphere, 2023)

Quantitative evaluation of variation and driving factors of the regional water footprint for cotton production in China - Qinqin Li; Weibin Huang; Jian Wang; Zhenggui Zhang; Yabing Li; Yingchun Han; Lu Feng; Xiaofei Li; Beifang Yang; Guoping Wang; Yaping Lei; Shiwu Xiong; et al. (Sustainable Production and Consumption, 2023)

Complexing agents-free bioelectrochemical trickling systems for highly-efficient mesothermal NO removal: The role of extracellular polymer substances - Xingzhu Huang; Shaofeng Zhou; Jianjun Li; Xiaojun Wang; Shaobin Huang; Guoping Sun; Shan Yang; Jia Xing; Meiying Xu (Bioresource Technology, 2023)

Ecological distribution of modern diatom in peatlands in the northern Greater Khingan Mountains and its environmental implications - Dongxue Han; Yang Sun; Jinxin Cong; Chuanyu Gao; Guoping Wang (Environmental Science and Pollution Research, 2022)

The AP2/ERF transcription factor SlERF.J2 functions in hypocotyl elongation and plant height in tomato - Yanan Chen; Hong Yang; Boyan Tang; Fenfen Li; Qiaoli Xie; Guoping Chen; Zongli Hu (Plant Cell Reports, 2022)

A quantitative analysis method for the degree of coupling coordination between drinking water carrying capacity and population spatial aggregation - Yuan Lei; Chen Guoping; Wang Jiasheng; Zhao Junsan; Yang Kun (Environment, Development and Sustainability, 2022)

Effect of maternal thallium exposure in early pregnancy on the risk of preterm birth - Xi Chen; Li Huang; Qian Li; Xu Zhang; Xiaoyi Wang; Guoqiang Sun; Nianhua Yi; Guoping Xiong; Xuefeng Yang; Liping Hao; Hongying Yang; Nianhong Yang (Environmental Science and Pollution Research, 2022)

Biological–physical processes regulate autumn prey availability of spiny icefish Chaenodraco wilsoni in the Bransfield Strait, Antarctic - Qingyuan Yang; Keith Reid; Guoping Zhu (Journal of Fish Biology, 2022)
This study examines the adaptability of a Southern Ocean predator, which is dependent on Antarctic krill ( Euphausia superba ), to potential changes in food availability. Muscle fatty acids (FAs) of the spiny icefish Chaenodraco wilsoni collected from three areas in the Bransfield Strait (BS), northern Antarctic Peninsula during February–April 2016 give a good representation of their feeding variability. The compositions of 22:6n3 (DHA) and 20:5n3 (EPA) were both higher in the Transitional Zonal Water with Bellingshausen influence (TBW)‐controlled C. wilsoni than in the Transitional Zonal Water with Weddell Sea influence (TWW)‐controlled fish. This was positively correlated with photoadaptation and carbon sequestration in TBW‐controlled phytoplankton. Results for the FAs 16:1n7, 16:0, DHA and EPA indicate the presence of dinoflagellates in all three areas, suggesting that during late summer and early fall, there is a seasonal phytoplankton succession, where small phytoplankton become dominant, in the BS. In addition, the compositions of some long‐chain FAs (>20, such as 20:0, 20:1, 22:0 and 22:1n9) and ∑18 indicated that the food chain based on flagellates and copepods was more apparent in TWW‐controlled C. wilsoni , especially the effect of El Niño‐Southern Oscillation (ENSO) on the variation of prey communities in TWW‐controlled areas. FA markers such as SFA/(PUFA+MUFA), ∑15 + ∑17 and ARA were more pronounced in TWW‐controlled C. wilsoni , indicating a more strongly carnivorous and benthic food source. In the TBW–TWW confluence, the complex hydrological structure, including the presence of a large number of mesoscale eddies, allows rich nutrients and krill larvae to remain in it, providing a rich food source for the C. wilsoni . Overall, the FA data of this study show that the diet of C. wilsoni varies in different marine environments, aiding their survivability at the face of climate change.

The rainfall thresholds and soil characteristics of large geological disasters in Zhejiang, China - Jin Ding; Guoping Zhang; Jinbing Gao; Shudong Wang; Bing Xue; Kuoyin Wang; Jing Yang; Ruijiao Jiang; Junbiao Lian (Arabian Journal of Geosciences, 2022)
Based on observed minute precipitation data during Lekima influencing Zhejiang (from 2019–08-07 00:00:00 to 2019–08-12 23:55:00), the rainfall thresholds for debris flow and landslide are investigated. The rainfall intensity and duration (I-D) thresholds are I = 1247.73D −403.44 + 19.09 and I = 142.63D −0.58 –3.37 for debris flow and landslide, respectively. Hourly meteorological data and soil data reveal that (1) the soil volume water content (SVWC) at deep soil layers (50–100 cm) fluctuated continuously during the occurrence of debris flow and landslide. At the end of the landslide period, SVWC at deep soil layers returned stable. (2) At the same soil layer, there was little difference between the upper adjacent values of SVWC in the periods of debris flow and landslide, but the lower adjacent values in the period of landslide were smaller. However, different from the distribution of soil moisture, the lower adjacent values of the soil temperature at all layers were basically the same when debris flow and landslide occurred, while the upper adjacent values were higher when landslide occurred than when debris flow occurred. (3) Compared with the whole typhoon influencing period and debris flow occurrence period, ground surface temperature and surface air temperature, soil temperature, and surface air temperature showed better correlations in landslide occurrence period. (4) Both during debris flow and landslide occurrence time, the soil temperature at all layers did not change with the change of soil depth. Soil temperature and moisture at shallow soil layers owned better correlations than at deep soil layers.

An integrated analysis of single-cell and bulk transcriptomics reveals EFNA1 as a novel prognostic biomarker for cervical cancer - Xiaopeng Shen; Meng Li; Yang Lei; Shan Lu; Sufen Wang; Zhongxian Liu; Chunguang Wang; Yun Zhao; Ao Wang; Chao Bi; Guoping Zhu (Human Cell, 2022)

Developmental Origins of Human Cortical Oligodendrocytes and Astrocytes - Lin Yang; Zhenmeiyu Li; Guoping Liu; Xiaosu Li; Zhengang Yang (Neuroscience Bulletin, 2022)
Human cortical radial glial cells are primary neural stem cells that give rise to cortical glutaminergic projection pyramidal neurons, glial cells (oligodendrocytes and astrocytes) and olfactory bulb GABAergic interneurons. One of prominent features of the human cortex is enriched with glial cells, but there are major gaps in understanding how these glial cells are generated. Herein, by integrating analysis of published human cortical single-cell RNA-Seq datasets with our immunohistochemistical analyses, we show that around gestational week 18, EGFR-expressing human cortical truncated radial glial cells (tRGs) give rise to basal multipotent intermediate progenitors (bMIPCs) that express EGFR, ASCL1, OLIG2 and OLIG1. These bMIPCs undergo several rounds of mitosis and generate cortical oligodendrocytes, astrocytes and olfactory bulb interneurons. We also characterized molecular features of the cortical tRG. Integration of our findings suggests a general picture of the lineage progression of cortical radial glial cells, a fundamental process of the developing human cerebral cortex.

Longitudinal virological changes and underlying pathogenesis in hospitalized COVID-19 patients in Guangzhou, China - Zhengtu Li; Yinhu Li; Ruilin Sun; Shaoqiang Li; Lingdan Chen; Yangqing Zhan; Mingzhou Xie; Jiasheng Yang; Yanqun Wang; Airu Zhu; Guoping Gu; Le Yu; et al. (Science China Life Sciences, 2021)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

The regular pattern and underlying mechanisms of seawater intrusion in the Modaomen channel in the Pearl River Estuary of China - Muzhen Yang; Guoping Tang; Tao Jiang; Tao Chen; Xiaohua Chen (Environmental Science and Pollution Research, 2021)

Wave-ice dynamical interaction: a numerical model and its application - Yang Zhang; Changsheng Chen; Guoping Gao; Jianhua Qi; Huichan Lin; Wei Yu; Liang Chang (Acta Oceanologica Sinica, 2021)

The full-length genome sequence of a novel mitovirus from Botryosphaeria dothidea, the causal agent of pear ring rot disease - Qi Zou; Yunjing Gao; Qiong Wang; Yuekun Yang; Fang Wang; Ni Hong; Guoping Wang; Liping Wang (Archives of Virology, 2021)

Transcription Factor VAX1 Regulates the Regional Specification of the Subpallium Through Repressing Gsx2 - Yan Wen; Zihao Su; Ziwu Wang; Lin Yang; Guoping Liu; Zicong Shang; Yangyang Duan; Heng Du; Zhenmeiyu Li; Yan You; Xiaosu Li; Zhengang Yang; et al. (Molecular Neurobiology, 2021)

Homeobox Gene Six3 is Required for the Differentiation of D2-Type Medium Spiny Neurons - Xiaolei Song; Haotian Chen; Zicong Shang; Heng Du; Zhenmeiyu Li; Yan Wen; Guoping Liu; Dashi Qi; Yan You; Zhengang Yang; Zhuangzhi Zhang; Zhejun Xu (Neuroscience Bulletin, 2021)
Medium spiny neurons (MSNs) in the striatum, which can be divided into D1 and D2 MSNs, originate from the lateral ganglionic eminence (LGE). Previously, we reported that Six3 is a downstream target of Sp8/Sp9 in the transcriptional regulatory cascade of D2 MSN development and that conditionally knocking out Six3 leads to a severe loss of D2 MSNs. Here, we showed that Six3 mainly functions in D2 MSN precursor cells and gradually loses its function as D2 MSNs mature. Conditional deletion of Six3 had little effect on cell proliferation but blocked the differentiation of D2 MSN precursor cells. In addition, conditional overexpression of Six3 promoted the differentiation of precursor cells in the LGE. We measured an increase of apoptosis in the postnatal striatum of conditional Six3 -knockout mice. This suggests that, in the absence of Six3, abnormally differentiated D2 MSNs are eliminated by programmed cell death. These results further identify Six3 as an important regulatory element during D2 MSN differentiation.

Influence of renal insufficiency on anticoagulant effects and safety of warfarin in Chinese patients: analysis from a randomized controlled trial - Xiaoyi Ning; Yun Kuang; Guoping Yang; Jinlian Xie; Da Miao; Chengxian Guo; Zhijun Huang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)
This study aimed to analyze the influence of renal insufficiency on the anticoagulant effects and safety of warfarin in Chinese patients. Data on the creatinine levels of participants enrolled in a randomized controlled study were screened and divided into the non-renal insufficiency group, mild renal insufficiency group, and moderate renal insufficiency group, according to the creatinine clearance rate. The primary outcome measures were stable dose and average daily dose of warfarin. Secondary outcome measures were percentage of time in the therapeutic international normalized ratio (INR) (%TTR), and the first time to reach the therapeutic INR. Adverse events included bleeding events, thromboembolic events, and mortality. All participants with renal function test results and a baseline INR of less than 1.5 were included in the primary and secondary outcome analysis. The SPSS Statistics 21.0 software was used for statistical analysis. The randomized controlled trial was registered in Clinicaltrials.gov (NCT02211326). A total of 571 patients were included in this analysis. Multiple regression analysis showed that the renal function was correlated with stable dose, average daily dose, and the first time to reach therapeutic INR after adjusting for confounding factors. However, no correlation was noted between kidney function and %TTR. No significant differences were observed across the various safety parameters among the three groups. Renal function is an important consideration in patients using warfarin.

Characteristics and Causes of Extreme Rainfall Induced by Binary Tropical Cyclones over China - Mingyang Wang; Fumin Ren; Yanjun Xie; Guoping Li; Ming-Jen Yang; Tian Feng (Asia-Pacific Journal of Atmospheric Sciences, 2021)
Binary tropical cyclones (BTC) often bring disastrous rainfall to China. From the viewpoint of the extreme of the BTC maximum daily rainfall, the characteristics of BTC extreme rainfall (BTCER) during 1960–2018 are analyzed, using daily rainfall data; and some representative large-scale mean flows, in which the associated BTCs are embedded, are analyzed. Results show that the frequency of BTCER shows a decreasing trend [−0.49 (10 yr) −1 ] and is mainly distributed within the BTC heavy rainstorm interval (100 mm ≤ BTCER

Decoding Cortical Glial Cell Development - Xiaosu Li; Guoping Liu; Lin Yang; Zhenmeiyu Li; Zhuangzhi Zhang; Zhejun Xu; Yuqun Cai; Heng Du; Zihao Su; Ziwu Wang; Yangyang Duan; Haotian Chen; et al. (Neuroscience Bulletin, 2021)
Mouse cortical radial glial cells (RGCs) are primary neural stem cells that give rise to cortical oligodendrocytes, astrocytes, and olfactory bulb (OB) GABAergic interneurons in late embryogenesis. There are fundamental gaps in understanding how these diverse cell subtypes are generated. Here, by combining single-cell RNA-Seq with intersectional lineage analyses, we show that beginning at around E16.5, neocortical RGCs start to generate ASCL1 + EGFR + apical multipotent intermediate progenitors (MIPCs), which then differentiate into basal MIPCs that express ASCL1, EGFR, OLIG2, and MKI67. These basal MIPCs undergo several rounds of divisions to generate most of the cortical oligodendrocytes and astrocytes and a subpopulation of OB interneurons. Finally, single-cell ATAC-Seq supported our model for the genetic logic underlying the specification and differentiation of cortical glial cells and OB interneurons. Taken together, this work reveals the process of cortical radial glial cell lineage progression and the developmental origins of cortical astrocytes and oligodendrocytes.

Study of the geostatistical grid maths operation method of quantifying water movement in soil layers of a cotton field * - Liyuan Liu; Fangfang Xing; Yabing Li; Yingchun Han; Zhanbiao Wang; Xiaoyu Zhi; Guoping Wang; Lu Feng; Beifang Yang; Yaping Lei; Zhengyi Fan; Wenli Du (Irrigation and Drainage, 2020)
The precise quantification of water movement in different field soil layers is important for variable‐rate irrigation and fertilization. To this end, a field experiment based on a geostatistical approach was conducted in southern Anyang, Henan, China, to examine soil water movement in a cotton field with drip irrigation by measuring the soil water content (SWC) data on a regular 100 × 80 cm grid. The result shows that the temporal and spatial variation of soil moisture decreased with the increase of soil depth at different points, and apparent spatial heterogeneity was observed under different soil conditions through a semivariogram analysis. The variation of soil moisture at different soil profiles was affected by the cotton plants and drip lines in non‐irrigation and irrigation periods respectively. The level of the change at 20 cm was more than 70 cm in the horizontal direction in the two periods, however the degree of change at 40 cm in the irrigation period was more than 70 cm in the vertical direction, while contrary results were shown in the non‐irrigation period. Moreover, the results indicated that the trapezoidal rule could be applied to quantify the volume of water movement precisely.

Molecular characterization of a novel mycovirus infecting the phytopathogenic fungus Botryosphaeria dothidea - Mengmeng Yang; Xiaoqi Zhou; Lifeng Zhai; Feng Xiao; Ni Hong; Guoping Wang (Archives of Virology, 2020)

Sideswiping Tropical Cyclones and Their Associated Precipitation over China - Tian Feng; Fumin Ren; Da-Lin Zhang; Guoping Li; Wenyu Qiu; Hui Yang (Advances in Atmospheric Sciences, 2020)

Optimized trio genome sequencing (OTGS) as a first-tier genetic test in critically ill infants: practice in China - Huijun Wang; Yulan Lu; Xinran Dong; Guoping Lu; Guoqiang Cheng; Yanyan Qian; Qi Ni; Ping Zhang; Lin Yang; Bingbing Wu; Wenhao Zhou (Human Genetics, 2020)

Cardiac-specific LRP6 knockout induces lipid accumulation through Drp1/CPT1b pathway in adult mice - Ying Wang; Chao Yin; Zhidan Chen; Yang Li; Yan Zou; Xiang Wang; Yanpeng An; Feizhen Wu; Guoping Zhang; Chunjie Yang; Huiru Tang; Yunzeng Zou; et al. (Cell and Tissue Research, 2020)

An Approach to Improve Soil Quality: a Case Study of Straw Incorporation with a Decomposer Under Full Film-Mulched Ridge-Furrow Tillage on the Semiarid Loess Plateau, China - Feng ke Yang; Baolin He; Ligong Zhang; Guoping Zhang; Yingping Gao (Journal of Soil Science and Plant Nutrition, 2020)

Characterization of a novel victorivirus isolated from the phytopathogenic fungus Botryosphaeria dothidea - Mengmeng Yang; Lifeng Zhai; Feng Xiao; Yashuang Guo; Min Fu; Ni Hong; Guoping Wang (Archives of Virology, 2019)

Thermal and saline tolerance of Antarctic krill Euphausia superba under controlled in-situ aquarium conditions - Guoping Zhu; Zijun Liu; Yang Yang; Zhen Wang; Wenjie Yang; Liuxiong Xu (Journal of Oceanology and Limnology, 2019)

Effects of Urban–rural Atmospheric Environment on Heavy Metal Accumulation and Resistance Characteristics of Pinus tabulaeformis in Northern China - Ruirui Zhao; Tong Yang; Cong Shi; Meili Zhou; Guoping Chen; Fuchen Shi (Bulletin of Environmental Contamination and Toxicology, 2019)

Determining the Effect of pH on the Partitioning of Neutral, Cationic and Anionic Chemicals to Artificial Sebum: New Physicochemical Insight and QSPR Model - Senpei Yang; Lingyi Li; Tao Chen; Lujia Han; Guoping Lian (Pharmaceutical Research, 2018)

Inferring trophic variation for Antarctic krill (Euphausia superba) in the Antarctic Peninsula from the austral fall to early winter using stable isotope analysis - Guoping Zhu; Haiting Zhang; Qi Song; Yang Yang; Shaoqin Wang; Qingyuan Yang (Acta Oceanologica Sinica, 2018)

Upper trophic structure in the Atlantic Patagonian shelf break as inferred from stable isotope analysis - Guoping Zhu; Haiting Zhang; Yang Yang; Shaoqin Wang; Lian Wei; Qingyuan Yang (Journal of Oceanology and Limnology, 2018)

Comparison of the Arctic upper-air temperatures from radiosonde and radio occultation observations - Liang Chang; Lixin Guo; Guiping Feng; Xuerui Wu; Guoping Gao; Yang Zhang; Yu Zhang (Acta Oceanologica Sinica, 2018)

Soil aggregate characteristics and stability of soil carbon stocks in a Pinus tabulaeformis plantation - Guoping Chen; Zhangying Gao; Lihong Zu; Lili Tang; Tong Yang; Xiaomei Feng; Tiejian Zhao; Fuchen Shi (New Forests, 2017)

Evaluation of forest structure, biomass and carbon sequestration in subtropical pristine forests of SW China - Syed Moazzam Nizami; Zhang Yiping; Zheng Zheng; Lu Zhiyun; Yang Guoping; Sha Liqing (Environmental Science and Pollution Research, 2017)

Whole transcriptome analysis of three leaf stages in two cultivars and one of their F1 hybrid of Camellia sinensis L. with differing EGCG content - Jinke Lin; Iain W. Wilson; Guoping Ge; Guiling Sun; Fuliang Xie; Yanfang Yang; Liangyu Wu; Baohong Zhang; Jianqiang Wu; Yue Zhang; Deyou Qiu (Tree Genetics & Genomes, 2017)

Identification of a divergent variant of grapevine berry inner necrosis virus in grapevines showing chlorotic mottling and ring spot symptoms - Xudong Fan; Ni Hong; Zunping Zhang; Zuokun Yang; Fang Ren; Guojun Hu; Zhengnan Li; Jun Zhou; Yafeng Dong; Guoping Wang (Archives of Virology, 2016)

Regulation signature of miR-143 and miR-26 in porcine Salmonella infection identified by binding site enrichment analysis - Min Yao; Weihua Gao; Hengxun Tao; Jun Yang; Guoping Liu; Tinghua Huang (Molecular Genetics and Genomics, 2016)

Genetic mapping and molecular marker development for the gene Pre2 controlling purple grains in barley - Qiaojun Jia; Jinghuan Zhu; Junmei Wang; Jianming Yang; Guoping Zhang (Euphytica, 2016)

Identification and expression analyses of calmodulin-binding transcription activator genes in soybean - Guoping Wang; Houqing Zeng; Xiaoyan Hu; Yiyong Zhu; Yang Chen; Chenjia Shen; Huizhong Wang; B. W. Poovaiah; Liqun Du (Plant and Soil, 2015)

Heavy metals and polycyclic aromatic hydrocarbons in sediments from the Shenzhen River, South China - Guoping Deng; Wenqing Yang; Guanye Zhou; Yun Li; Shili Liu (Environmental Science and Pollution Research, 2014)

Mapping the Time Course of Other-Race Face Classification Advantage: A Cross-Race ERP Study - Gang Sun; Guoping Zhang; Yanjie Yang; Shlomo Bentin; Lun Zhao (Brain Topography, 2014)

Senescent endothelial dysfunction is attributed to the up-regulation of sphingosine-1-phosphate receptor-2 in aged rats - Hongwei Lu; Hong Yuan; Shuhua Chen; Lihua Huang; Hong Xiang; Guoping Yang; Hao Deng; Jun Zhou (Molecular and Cellular Biochemistry, 2012)

In vitro antimicrobial activity of the leaf essential oil of Spiraea alpina Pall. - Yun Teng; Qian Yang; Zhiyi Yu; Guoping Zhou; Qiu Sun; Hong Jin; Taiping Hou (World Journal of Microbiology and Biotechnology, 2010)

The role of extracellular matrix, integrins, and cytoskeleton in mechanotransduction of centrifugal loading - Juan Li; Zhihe Zhao; Jun Wang; Guoping Chen; Jingyuan Yang; Songjiao Luo (Molecular and Cellular Biochemistry, 2008)

Characterization of Heavy Metals and Sulphur Isotope in Water and Sediments of a Mine-Tailing Area Rich in Carbonate - Guoping Zhang; Cong-Qiang Liu; Yuangen Yang; Pan Wu (Water, Air, & Soil Pollution, 2004)

Construction of Double-Copy Glucose Isomerase Gene Engineering Strain of Streptomyces diastaticus by Homologous Recombination - Ying Zhang; Chong Xu; Zhiqiang Lu; Yonghui Yang; Feng Ge; Guoping Zhu; Maikun Teng; Liwen Niu (Current Microbiology, 2002)

Site-Specific Integration of the Double-Mutation Glucose Isomerase (GIG138PG247D) Gene in Streptomyces lividans and Its Stable Expression - Yonghui Yang; Chong Xu; Feng Ge; Zhiqiang Lu; Guoping Zhu; Hui Li; Jun Liao; Liwen Niu; Yuzhen Wang; Mian Wu (Current Microbiology, 2002)

Heterologous Expression of the Single-Mutation Glucose Isomerase (GIG138P) Gene in Streptomyces lividans and Its Genetic Instability - Yonghui Yang; Chong Xu; Feng Ge; Zhiqiang Lu; Guoping Zhu; Hui Li; Jun Liao; Maikun Teng; Liwen Niu; Yuzhen Wang (Current Microbiology, 2001)